Search for supersymmetry at the LHC in events with jets and missing transverse energy - Chatrchyan, S. (2011)
A search for events with jets and missing transverse energy is performed in a data sample of pp collisions collected at √s=7TeV by the CMS experiment at the LHC. The analyzed data sample corresponds to an integrated luminosity of 1.14fb-1. In this search, a kinematic variable αT is used as the main discriminator between events with genuine and misreconstructed missing transverse energy. No excess of events over the standard model expectation is found. Exclusion limits in the parameter space of the constrained minimal supersymmetric extension of the standard model are set. In this model, squark masses below 1.1 TeV are excluded at 95% C.L. Gluino masses below 1.1 TeV are also ruled out at 95% C.L. for values of the universal scalar mass parameter below 500 GeV. © 2011 CERN.